Strategi Pengembangan Produk UMKM Kerupuk Sagu di Desa Jerambang Kecamatan Gaung - Rumiati; Putri, Resi Dwi; Syahriansyah, M.Alfi; Azzikrie, Teguh Wajar; Nur Amin, Muhammad; Nuralamsyah, Fikri; Adi Putra, Bambang Sasmita (Indra Institute Research & Publication, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector plays a strategic role in supporting economic stability. MSMEs offer an alternative business model for improving the welfare of entrepreneurs, fostering technological development, absorbing labor with relatively low capital, and preserving a culture that is resistant to product modernization. This study aims to examine the product development strategy of MSMEs producing sago crackers in Jerambang Village, Gaung District, Indragiri Hilir Regency. The method used was descriptive qualitative, using surveys, observations, and interviews. The results indicate that the Bu Ulfa Sago Cracker MSME faces several challenges, including a lack of business permits, unattractive packaging, and conventional marketing. To address these challenges, several development strategies were implemented, including creating a logo and brand to create a clear product identity, developing stronger and more attractive packaging, registering a business permit through the OSS (Owner-Owned Enterprises) to obtain legality, and creating social media and marketplace accounts to expand marketing. These strategies have been proven to increase product competitiveness, expand market reach, and open up greater business opportunities. This study recommends continuous innovation and strengthening digital marketing to support business sustainability.